Analisis Pengaruh Citra Merek, Desain Kemasan, dan Harga terhadap Loyalitas Pelangan Melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Produk Minuman Bersoda Sprite - Fikia Siti Meisaroh; Rusdi Hidayat Nugroho; Sonja Andarini; Lia Nirawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to examine and analyze the effect of brand image, packaging design, and price on customer loyalty through customer satisfaction as an intervening variable on sprite soda products. The population in this study was the people of Surabaya City who had bought and drank Srite products in the city of Surabaya. The number of samples used in this study were 100 respondents. The sampling technique used is a non-probability sampling technique. This type of research uses descriptive quantitative. The results of this study indicate that brand image has a significant effect on customer satisfaction. Packaging design has a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction, brand image has a significant effect on customer loyalty. Price has a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Brand image has no significant effect on customer loyalty through customer satisfaction. Satisfaction design has no significant effect on customer loyalty through customer satisfaction. Price has a significant effect on customer loyalty through customer satisfaction. Keywords: Brand Image; Packaging Design; Price; Customer loyalty; Customer satisfaction